Una especie nueva del género Astrocasia (Euphorbiaceae) del estado de Guerrero, México - Jiménez Ramírez, Jaime; Martínez Gordillo, Martha (Instituto de Ecología, A.C., 2001)
Astrocasia diegoae, a new species from Guerrero, Mexico, is described and illustrated. This new taxon is distinguished from the other five known species of Astrocasia in being a monoecious subshrub, having the sepals and petals of almost the same size, and occasionally possessing bisexual inflorescences. A key is provided for the identification of the four species of Astrocasia known from Mexico. Astrocasia neurocarpa is reported for the first time from the state of Guerrero. Although the genus Astrocasia has been considered essentially dioecious, this notion is altered by the existence of this new monoecious species, as well as the presence of monoecious individuals of A. neurocarpa in Guerrero.